Developing a Pre-Implementation Model for the ERP Material Management Module in the PVC Supply Industry in Indonesia - Luis, -; Sutomo, Rudi (Society of Visual Informatics, 2025)
Rapid technological advancements have transformed the business landscape by introducing systems that enable more efficient and integrated operational management. One increasingly popular solution is Enterprise Resource Planning (ERP), which helps companies comprehensively manage business activities. However, many companies still face challenges in adopting ERP technology, particularly in managing inventory effectively and efficiently. One such company is PVC Supply Industry, which uses manual inventory recording. This research addresses the issues faced by the PVC Supply Industry as a case study to analyze pre-implementation ERP before transitioning to ERP implementation. The study begins with a literature review to identify 20 relevant ERP and inventory management indicators using the Semantic Scholar database. These 20 indicators were then included in a questionnaire distributed to individuals or groups with experience or understanding of ERP/IT. The responses were analyzed using the SmartPLS application, utilizing the IS success model, and categorizing the 20 indicators into four areas: people, process, technology, and ERP implementation readiness. The research results will provide four dominant indicators from these areas based on the SmartPLS analysis. The dominant indicators are P3 (human resource management), PC4 (material requirement planning), TC3 (prototype), and RE (ERP system implementation). These indicators will be applied to a Figma prototype using the prototyping method. The Figma prototype is designed to offer a rough user interface of the ERP material management module to address the issues encountered by the PVC Supply Industry as a case study.